Ethics of stem cell‐derived gametes made in a dish: fertility for everyone?. Issue 4 (9th March 2017) - Bredenoord, Annelien L; Hyun, Insoo
Abstract : A timely and thoughtful discussion of the ethical challenges and societal impacts presented by the recent reports demonstrating the successful in vitro generation of functional gametes from somatic and pluripotent stem cells.